Understanding school food provision in the Pacific: Scoping the potential of local food systems to improve diets, nutrition and livelihoods (2022-2024) - Hunter, Danny; Burkhart, Sarah; Ranieri, J. (2024)
Presented at the Grassroots Partnerships for Pacific Solutions Conference in Nuku’alofa, Tonga, between 16-20 September. This presentation highlights findings from a scoping study which aimed to understand the current state of local agriculture into school food provision in the Pacific Islands region and the current policy landscape and enabling environment for integration of local agriculture into school food provision; to identify the best-bet sustainable options for integrating local agriculture in school food provision and recommendations for future action and to build awareness and consensus around the multiple benefits of integrating local agriculture in school food provision and identify partnerships for collective action on key next steps.